Urban plan as a precondition for continuous and directed development – the example of the Nikola Tesla Airport - Lalošević, Marija D.; Đerić, Jelena (Industrija, 2022)
Abstract: Belgrade Nikola Tesla Airport, as a complex of strategic importance for the Republic of Serbia, has been the subject of planning, study and design elaboration through several urban planning documents in different periods. Although the realization of the basic planning settings for the development of Belgrade Airport, formulated in 1972 and 1985, was accompanied by economic difficulties and changes in the dynamics and phases of realization, the strategic concept of development of this complex remained unchanged. Further development of the airport through the construction of the second runway, improvement of existing and construction of new facilities in order to increase capacity, monitor trends in air traffic development and growth of passenger and goods traffic, was confirmed through the Master Plan of Belgrade and the Plan of General Regulation of the building area of local self-government units’ seats – City od Belgrade, both documents from 2016. A new planning document, the Plan of Detailed Regulation for the airport „Nikola Tesla Belgrade“, was adopted in 2020. The Paper analyzes the spatial conditions, gives a historical overview of planning and realization of the area and presents the urban planning solutions for the development of the Airport "Nikola Tesla Belgrade", with a planning horizon until 2043.
Keywords: air traffic, airport, Nikola Tesla Belgrade, runway, urban plan